Exporters, Engineers, and Blue-Collar Workers - Brambilla, Irene; Lederman, Daniel; Porto, Guido (World Bank, Washington, DC, 2016)
This paper investigates differences in the composition of employment between exporting and non-exporting firms. In particular, it asks whether exporting firms hire more engineers relative to blue-collar workers than non-exporting firms. In a stylized partial-equilibrium model, firms produce goods of varying quality and exporters tend to produce higher quality goods, which are intensive in engineers relative to blue-collar workers. Firms are heterogeneous and more productive firms become exporters and have a higher demand for engineers. The paper provides causal evidence in support of these theories using the Chilean Encuesta Nacional Industrial Anual, an annual census of manufacturing firms. The results from an instrumental variable estimator suggest that Chilean exporters indeed utilize a higher share of engineers over blue-collar workers.